Screening Mammography for Women Aged 40 to 49 Years at Average Risk for Breast Cancer: An Evidence-Based Analysis (Medical Advisory Secretariat, 2007)
OBJECTIVE: The aim of this review was to determine the effectiveness of screening mammography in women aged 40 to 49 years at average risk for breast cancer. CLINICAL NEED: The effectiveness of screening mammography in women aged over 50 years has been established, yet the issue of screening in women aged 40 to 49 years is still unsettled. The Canadian Task Force of Preventive Services, which sets guidelines for screening mammography for all provinces, supports neither the inclusion nor the exclusion of this screening procedure for 40- to 49-year-old women from the periodic health examination. In addition to this, 2 separate reviews, one conducted in Quebec in 2005 and the other in Alberta in 2000, each concluded that there is an absence of convincing evidence on the effectiveness of screening mammography for women in this age group who are at average risk for breast cancer. In the United States, there is disagreement among organizations on whether population-based mammography should begin at the age of 40 or 50 years. The National Institutes of Health, the American Association for Cancer Research, and the American Academy of Family Physicians recommend against screening women in their 40s, whereas the United States Preventive Services Task Force, the National Cancer Institute, the American Cancer Society, the American College of Radiology, and the American College of Obstetricians and Gynecologists recommend screening mammograms for women aged 40 to 49 years. Furthermore, in comparing screening guidelines between Canada and the United States, it is also important to recognize that “standard care” within a socialized medical system such as Canada’s differs from that of the United States. The National Breast Screening Study (NBSS-1), a randomized screening trial conducted in multiple centres across Canada, has shown there is no benefit in mortality from breast cancer from annual mammograms in women randomized between the ages of 40 and 49, relative to standard care (i.e. physical exam and teaching of breast-self examination on entry to the study, with usual community care thereafter). At present, organized screening programs in Canada systematically screen women starting at 50 years of age, although with a physician’s referral, a screening mammogram is an insured service in Ontario for women under 50 years of age. International estimates of the epidemiology of breast cancer show that the incidence of breast cancer is increasing for all ages combined, whereas mortality is decreasing, though at a slower rate. These decreasing mortality rates may be attributed to screening and advances in breast cancer therapy over time. Decreases in mortality attributable to screening may be a result of the earlier detection and treatment of invasive cancers, in addition to the increased detection of ductal carcinoma in situ (DCIS), of which certain subpathologies are less lethal. Evidence from the SEER cancer registry in the United States indicates that the age-adjusted incidence of DCIS has increased almost 10-fold over a 20-year period (from 2.7 to 25 per 100,000). The incidence of breast cancer is lower in women aged 40 to 49 years than in women aged 50 to 69 years (about 140 per 100,000 versus 500 per 100,000 women, respectively), as is the sensitivity (about 75% versus 85% for women aged under and over 50, respectively) and specificity of mammography (about 80% versus 90% for women aged under and over 50, respectively). The increased density of breast tissue in younger women is mainly responsible for the lower accuracy of this procedure in this age group. In addition, as the proportion of breast cancers that occur before the age of 50 are more likely to be associated with genetic predisposition as compared with those diagnosed in women after the age of 50, mammography may not be an optimal screening method for younger women. Treatment options vary with the stage of disease (based on tumor size, involvement of surrounding tissue, and number of affected axillary lymph nodes) and its pathology, and may include a combination of surgery, chemotherapy, and/or radiotherapy. Surgery is the first-line intervention for biopsy confirmed tumours. The subsequent use of radiation, chemotherapy, or hormonal treatments is dependent on the histopathologic characteristics of the tumor and the type of surgery. There is controversy regarding the optimal treatment of DCIS, which is noninvasive. With such controversy as to the effectiveness of mammography and the potential risk associated with women being overtreated or actual cancers being missed, and the increased risk of breast cancer associated with exposure to annual mammograms over a 10-year period, the Ontario Health Technology Advisory Committee requested this review of screening mammography in women aged 40 to 49 years at average risk for breast cancer. This review is the first of 2 parts and concentrates on the effectiveness of screening mammography (i.e., film mammography, FM) for women at average risk aged 40 to 49 years. The second part will be an evaluation of screening by either magnetic resonance imaging or digital mammography, with the objective of determining the optimal screening modality in these younger women. REVIEW STRATEGY: The following questions were asked: Does screening mammography for women aged 40 to 49 years who are at average risk for breast cancer reduce breast cancer mortality? What is the sensitivity and specificity of mammography for this age group? What are the risks associated with annual screening from ages 40 to 49? What are the risks associated with false positive and false negative mammography results? What are the economic considerations if evidence for effectiveness is established? The Medical Advisory Secretariat followed its standard procedures and searched these electronic databases: Ovid MEDLINE, EMBASE, Ovid MEDLINE In-Process and Other Non-Indexed Citations, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews and the International Network of Agencies for Health Technology Assessment. Keywords used in the search were breast cancer, breast neoplasms, mass screening, and mammography. In total, the search yielded 6,359 articles specific to breast cancer screening and mammography. This did not include reports on diagnostic mammograms. The search was further restricted to English-language randomized controlled trials (RCTs), systematic reviews, and meta-analyses published between 1995 and 2005. Excluded were case reports, comments, editorials, and letters, which narrowed the results to 516 articles and previous health technology policy assessments. These were examined against the criteria outlined below. This resulted in the inclusion of 5 health technology assessments, the Canadian Preventive Services Task Force report, the United States Preventive Services Task Force report, 1 Cochrane review, and 8 RCTs. INCLUSION CRITERIA: English-language articles, and English and French-language health technology policy assessments, conducted by other organizations, from 1995 to 2005. Articles specific to RCTs of screening mammography of women at average risk for breast cancer that included results for women randomized to studies between the ages of 40 and 49 years. Studies in which women were randomized to screening with or without mammography, although women may have had clinical breast examinations and/or may have been conducting breast self-examination. UK Age Trial results published in December 2006. EXCLUSION CRITERIA: Observational studies, including those nested within RCTs. RCTs that do not include results on women between the ages of 40 and 49 at randomization. Studies in which mammography was compared with other radiologic screening modalities, for example, digital mammography, magnetic resonance imaging or ultrasound. Studies in which women randomized had a personal history of breast cancer. INTERVENTION: Film mammography. COMPARATORS: Within RCTs, the comparison group would have been women randomized to not undergo screening mammography, although they may have had clinical breast examinations and/or have been conducting breast self-examination. OUTCOMES OF INTEREST: Breast cancer mortality. SUMMARY OF FINDINGS: There is Level 1 Canadian evidence that screening women between the ages of 40 and 49 years who are at average risk for breast cancer is not effective, and that the absence of a benefit is sustained over a maximum follow-up period of 16 years. All remaining studies that reported on women aged under 50 years were based on subset analyses. They provide additional evidence that, when all these RCTs are taken into account, there is no significant reduction in breast cancer mortality associated with screening mammography in women aged 40 to 49 years. CONCLUSIONS: There is Level 1 evidence that screening mammography in women aged 40 to 49 years at average risk for breast cancer is not effective in reducing mortality. Moreover, risks associated with exposure to mammographic radiation, the increased risk of missed cancers due to lower mammographic sensitivity, and the psychological impact of false positives, are not inconsequential. The UK Age Trial results published in December 2006 did not change these conclusions.